Praxeological analysis in Indonesian and Singaporean mathematics textbooks: An understanding geometrical similarity by students - Kuncoro, Krida Singgih; Suryadi, Didi; Dahlan, Jarnawi Afgani; Jupri, Al (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Mathematics textbooks are essential tools for facilitating the achievement of learning objectives, yet their use varies across classrooms, even when the same mathematical concepts are being taught. This study aims to investigate students' understanding of geometrical similarity through praxeological analysis within the framework of the Anthropological Theory of the Didactic (ATD). The analysis identifies differences in the structuring of geometrical similarity tasks between Indonesian and Singaporean textbooks. According to ATD praxeology, mathematical content is analyzed through the